Musashi-2 and related stem cell proteins in the mouse suprachiasmatic nucleus and their potential role in circadian rhythms. Issue 75 (June 2019) - Beligala, Dilshan H.; De, Arpan; Malik, Astha; Silver, Rae; Rimu, Kania; LeSauter, Joseph; McQuillen, Hugh J.; Geusz, Michael E.
Highlights: Stem cell proteins MSI2 and OCT4 are expressed in SCN neurons and glial cells. Cytoskeletal components SOX2, GFAP, vimentin, and nestin are co-expressed in SCN. SCN astrocytes may promote the stem-like state through Notch and MSI2 signaling. Circadian rhythms continue while SCN stem-like cells proliferate in vitro. MSI2 and similar RNA-binding proteins may regulate stem-like circadian clocks cells. Abstract: Background: The suprachiasmatic nucleus (SCN) of the mammalian hypothalamus contains the master circadian clock of the body and an unusually large number of cells expressing stem cell-related proteins. These seemingly undifferentiated cells may serve in entrainment of the SCN circadian clock to light cycles or allow it to undergo neural plasticity important for modifying its rhythmic output signals. These cells may also proliferate and differentiate into neurons or glia in response to episodic stimuli or developmental events requiring alterations in the SCN's control of physiology and behavior. Problem: To characterize expression of stem cell related proteins in the SCN and the effects of stem-like cells on circadian rhythms. Methods: Explant cultures of mouse SCN were maintained in medium designed to promote survival and growth of stem cells but not neuronal cells. Several stem cell marker proteins including SRY-box containing gene 2 (SOX2), nestin, vimentin, octamer-binding protein 4 (OCT4), and Musashi RNA-binding protein 2 (MSI2) were identified by immunocytochemistry in histological sections from adult mouse SCN and in cultures of microdissected SCN. A bioinformatics analysis located potential SCN targets of MSI2 and related RNA-binding proteins. Results: Cells expressing stem cell markers proliferated in culture. Immunostained brain sections and bioinformatics supported the view that MSI2 regulates immature properties of SCN neurons, potentially providing flexibility in SCN neural circuits. Explant cultures had ongoing mitotic activity, indicated by proliferating-cell nuclear antigen, and extensive cell loss shown by propidium iodide staining. Cells positive for vasoactive intestinal polypeptide (VIP) that are highly enriched in the SCN were diminished in explant cultures. Despite neuronal cell loss, tissue remained viable for over 7 weeks in culture, as shown by bioluminescence imaging of explants prepared from SCN of Per1::luc transgenic mice. The circadian rhythm in SCN gene expression persisted in brain slice cultures in stem cell medium. Prominent, widespread expression of RNA-binding protein MSI2 supported the importance of posttranscriptional regulation in SCN functions and provided further evidence of stem-like cells. Conclusion: The results show that the SCN retains properties of immature neurons and these properties persist in culture conditions suitable for stem cells, where the SCN stem-like cells also proliferate. These properties may allow adaptive circadian rhythm adjustments. Further exploration should examine stem-like cells of the SCN in vivo, how they may affect circadian rhythms, and whether MSI2 serves as a master regulator of SCN stem-like properties.